Family-school relationship: meanings of rural teachers on the participation of families - Fernández Vega, Juan Pablo (2021)
The purpose of this study is to reveal the meanings of the family-school relationship, specifically in the field of participation, from the perspective of teachers who work in rural schools in the commune of Bulnes, Chile. From the methodological point of view, the qualitative study is placed under the comprehensive interpretive paradigm, the data production technique corresponds to the semi-structured interview in a single session. The analysis of the discourses is developed through semantic structural analysis. Among the findings we have that: about parenting, the absence of norms from a permissive style is noted, the importance of the teacher's role in working with the psychosocial couple. Regarding volunteering, its facilitators are the proper functioning of a school, which has positive effects on learning and motivation. Finally, it is concluded that a well-organized school promotes a family-school relationship with shared responsibilities, which has positive academic and socio-emotional effects on its students.